Brachial Plexus' Schwannoma in a Child - Papa Alassane Mbaye; Cheikh Seye; Florent Tshibwid A. Zeng; Gabriel Ngom (Wolters Kluwer Medknow Publications, 2022)
Children's schwannoma is a rare condition, generally occurring in a sporadic way. Its aetiology is still not fully understood. We report the case of a 10-year old girl who presented a left shoulder mass, along motility reduction of the left upper limb for 24 months before presentation at our service. A biopsy resection of the mass gave the diagnosis and 6 months after surgical resection, no complication occurred.